(untitled) - Martyshev, F. G. (India, 1993)
A comprehensive study of pond fisheries. Topics include the organisation and construction of fish ponds, production processes in fish farms for warmwater carp and cold-water trout, and irrigation networks and reservoirs constructed for multipurpose exploitation.
Keywords: Fish ponds,Fish-culture